Vehicle-based in-situ observations of the water vapor isotopic composition across China during the monsoon season 2018 - Wang, Di; Tian, Lide (PANGAEA, 2022)
This dataset provide large scale (order 10000 km) vehicle-based in-situ observations of near-surface water vapor isotopic composition and concurrent meteorological data across China during the pre-monsoon season 2018 (28th July to 18th August, 2018). We used a Picarro 2130i CRDS water vapor isotope analyzer fixed on a vehicle to obtain continuous measurements of near-surface vapor isotopes (δ18O and δ2H) and vapor concentration (humidity) along the route. All measured vapor isotope values were humidity calibrated and also calibrated to the VSMOW-SLAP scale. The position data (latitude, longitude, and altitude) along the route are recorded by a portable GPS unit. Air temperature (T), relative humidity (RH), dew-point temperature (Td), and air pressure (Pres) are measured by a portable weather station on the roof of the vehicle. All sensors were located near the ambient air intake. The specific humidity (q) of the near-surface air was calculated from the measured Td and Pres. Meteorological data, GPS location data and vapor isotope data were synchronized according to their measurement times. Average precipitation during the observation period (P- temporal mean) and daily precipitation (P-daily) from the Global Precipitation Climatology Project (GPCP) are also provided. The dataset present here had been averaged to a 10-min temporal resolution, with the horizontal footprint of about 15 km. Based on the tracking results of the HYSPLIT4 model, we classify the observations into different potential sources of water vapor based on the geographical origin of the air masses and label them with different area numbers. During the monsoon period, we categorize our domain into 4 regions: (1) SR_1: In northwestern China, most air masses also spend considerable time over the continent, suggesting some of the vapor can be recycled by continental recycling. (2) SR_2: In northeastern China, trajectories mainly come from the North and though the Westerlies. (3) SR_3: In central China, both in its eastern (from Beijing to Harbin) and western part, trajectories mainly come from the East. This suggests that vapor mainly comes from the Pacific Ocean, or from continental recycling over eastern and central China. (4) SR_4: In southeastern China, trajectories come from the South, suggesting marine moisture sources from the Arabian Sea and the BoB.
Keywords: China; East Asia; in-situ observations; Seasonal difference; Spatial distribution; Vapor isotopes; Vehicle-based